The Relationship between Knowledge and Behavior of Pregnant Women in Preparing for Childbirth at the Mamuju Community Health Center - Rabuana, Susi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Various health elements are directly involved in the care of mothers and babies, such as doctors, midwives and nurses, or supporting elements, such as community organizations, which will support the EMAS Program. It is hoped that the preparation for childbirth that will be carried out with a midwife can reduce the mother's unpreparedness during childbirth and increase the mother's receipt of optimal care. The aim of the research was to determine the relationship between knowledge and the behavior of pregnant women in preparation for childbirth. This research method is analytical descriptive research with a cross sectional design. The population is all pregnant women, totaling 57 pregnant women. The research sample is the total population, namely 57 pregnant women. Data analysis used the Chi-square test. The results of the study showed that the majority of pregnant women had good knowledge, 31 (54.4%) and the behavior of pregnant women in preparing for delivery was mostly positive behavior, 44 (77.2%), the results of the X² table statistical test were 5,591 and the calculated X² was 11,339, meaning that the calculated X² value is greater than the table X² value and the p value = 0.003 or smaller than α = 0.05 with a confidence interval of 95%. Conclusion: there is a relationship between knowledge and the behavior of pregnant women in preparing for childbirth at the Mamuju Community Health Center.